2016
DOI: 10.3329/bjmed.v27i1.28071
|View full text |Cite
|
Sign up to set email alerts
|

Mortality Burden of Non Communicable Disease – A Retrospective Study In A Tertiary Care Hospital of Bangladesh

Abstract: Pattern of mortality gives a picture of disease burden of a community and helps in evaluation of health care system. A retrospective study was done in medicine wards of a tertiary care hospital in Bangladesh from 1st July 2014 to 30st June 2015 to see the mortality pattern. Data obtained from death and admission registrar. Total 1306 deaths were recorded. Mortality rate was 7%. Male female ratio was 1.65:1. Average age at death was 56.05 years. Highest 11.3% death occurred in January, 48.6% deaths occurred dur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 6 publications
1
2
0
Order By: Relevance
“…Our document analysis of 2 major hospitals in Dhaka city showed that 45.9% of the deaths in 2014 were due to CVDs, RTIs, other accidents or injuries, and suicidal attempts. This is similar to the findings in other parts of Bangladesh [15,18,28,29]. These analyses showed also that the number of deaths from medical emergencies increased over the last decades in the country.…”
Section: Burden Of Diseases In Dhaka Related To Deficient Emrssupporting
confidence: 89%
See 2 more Smart Citations
“…Our document analysis of 2 major hospitals in Dhaka city showed that 45.9% of the deaths in 2014 were due to CVDs, RTIs, other accidents or injuries, and suicidal attempts. This is similar to the findings in other parts of Bangladesh [15,18,28,29]. These analyses showed also that the number of deaths from medical emergencies increased over the last decades in the country.…”
Section: Burden Of Diseases In Dhaka Related To Deficient Emrssupporting
confidence: 89%
“…These analyses showed also that the number of deaths from medical emergencies increased over the last decades in the country. Particularly the increase of CVDs in urban Bangladesh has reached alarming levels [15,18,28,30]. Also deaths due to disasters such as building collapse, fire, gas explosion, occupational accidents are increasingly important [12,14,17,31].…”
Section: Burden Of Diseases In Dhaka Related To Deficient Emrsmentioning
confidence: 99%
See 1 more Smart Citation